Islam and Poverty Reduction Strategies: Attempts at Dealing with Poverty in the Ghanaian Muslim Community - Ammah, Rabiatu 19XX- (Ghana bulletin of theology, 2007)
There seems to be an assumption or perception that Muslims in Ghana are poor, though this is a debatable issue. For some, it is a perception and must remain as such since poverty is not peculiar to Muslims alone. On the contrary, it has also been suggested that though, relatively there may be under development in predominantly Muslim areas, the community is not pulling its weight in the fight against poverty. Muslims may even be perpetuating it unconsciously by their general lifestyles and attitudes. Granted that it is real, the fundamental question remains: What efforts are Muslims making to improve their lot through the implementation of the resources in the Qur'an and Sunna?